Application of the Bona Fide Principle in the Implementation of the Binding Sale and Purchase Agreement Related to the Seller’s Absence Before the Notary-PPAT - Adistia, Meisya; Ridwan, Fully Handayani (JURNAL AKTA, 2025)
The Sale and Purchase Agreement (in Indonesian Version: Perjanjian Pengikatan Jual Beli (PPJB)) is a crucial foundation before the formation of the Akta Jual Beli (AJB). However, in practice, serious obstacles often arise when the seller is unable to be present before the Notary-PPAT. This phenomenon not only hinders administrative processes but also potentially undermines the validity of the deed, increases the risk of breach of contract, and weakens the legal protection that the buyer should receive. In this complex situation, the principle of bona fide (itikad baik) becomes a fundamental pillar that demands honesty, transparency, and compliance with legal obligations from all parties involved. This study uses a doctrinal method to analyze legislation, legal doctrines, and evaluate how court decisions (case studies of Decision Number 28/Pdt/2022/PT SMG, Decision Number 20/Pdt.G/2023/PN.Tgt, and Decision Number 36/PDT/2020/PT.Smg) refer to the principle of bona fide in cases of seller absence in PPJB, and to what extent these decisions can serve as a basis or consideration in choosing dispute resolution mechanisms (litigation, mediation, or arbitration). In-depth analysis shows that judicial bodies consistently emphasize the importance of the principle of bona fide and deed formality. The main results of the analysis indicate that these decisions, by reinforcing the validity of the deed or highlighting violations of good faith, implicitly and explicitly encourage the parties to consider alternative dispute resolution methods such as mediation or arbitration as faster, more efficient efforts that potentially maintain good relations, while striving to reach agreements reflecting the principle of bona fide for legal certainty.